Adapting Design Thinking for Medical IoT: A Scoping Review of Iterative Frameworks in Geriatric Healthcare - Dhika Dharmansyah; Laili Rahayuwati; Iqbal Pramukti; Kuswandewi Mutyara; Ariani Arista Putri Pertiwi (LP3M Universitas Muhammadiyah Tasikmalaya, 2025)
The aging global population, projected to reach 22% by 2050, necessitates innovative healthcare technologies tailored to elderly users. While Medical Internet of Things (IoT) systems offer promising solutions for geriatric care, their development faces significant challenges including usability limitations and cybersecurity vulnerabilities. This scoping review examines how Design Thinking (DT) frameworks can be adapted to address the unique requirements of elderly-centric embedded systems development. A systematic scoping review following Joanna Briggs Institute methodology was conducted using SCOPUS database searches. Boolean operators combined keywords related to Design Thinking, elderly and Internet of Things. Inclusion criteria encompassed peer-reviewed studies (2015-2025) and grey literature addressing iterative design modifications for elderly populations, excluding non-English publications and systems without embedded sensor components. From 106 initial records, 10 studies met inclusion criteria after systematic screening. Key modifications to traditional DT phases included deeper user involvement, slower pacing, real-world validation, inclusive engagement strategies, co-design methodologies, and enhanced ethical considerations throughout development processes. Modified DT frameworks for elderly IoT development require prioritizing inclusive, context-aware, and iterative processes. Co-design approaches, real-world validation, and ongoing stakeholder support are essential for creating accessible, accepted, and effective solutions that address the complex physiological, cognitive, and socio-technical challenges faced by aging populations